The application of AHP in the development of a taxonomy of merchant marine deck officers’ non-technical skills (NTS) - Saeed, Farhan (Logistics and sustainable transport, 2019)
The importance of NTS has been realised in many safety critical industries. Recently the maritime domain has also embraced the idea and implemented an NTS training course for both merchant marine deck and engineering officers. NTS encompass both interpersonal and cognitive skills such as situational awareness, teamwork, decision making, leadership, managerial skills, communication and language skills. Well-developed NTS training allow ship’s officers to recognise quickly when a problem is developing and manage the situation safely and efficiently with the available team members. As a result, the evaluation and grading of deck officers’ NTS is necessary to assure safety at sea, reduce the effects of human error on-board ships, and allow ship board operations to be performed safely. This paper identifies the skills necessary for deck officers to effectively perform their duties on the bridge of a ship. To achieve this, initially, a taxonomy of deck officers’ NTS is developed through a review of relevant literature and the conducting of semi-structured interviews with experienced seafarers. Subsequently, NTS weighting data is collected from experienced seafarers to allow the weight of each element of the taxonomy to be established by the use of the Analytical Hierarchy Process (AHP).
Keywords: analitični hierarhični proces; analytical hierarchy process; človeški element; human element; leadership; netehnične veščine; non-technical skills; vodenje